2018
DOI: 10.1097/aap.0000000000000870
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Tobacco Cigarette Smoking on Spinal Cord Stimulation Effectiveness in Chronic Spine–Related Pain Patients

Abstract: Among our SCS-implanted sample, a positive correlation was observed between tobacco use and degree of pain reduction as early as 12 months postimplant; this was evident by the reported higher pain scores and opioid use in current smokers in comparison with former smokers and lifelong nonsmokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 51 publications
(56 reference statements)
1
19
0
Order By: Relevance
“…This is particularly true for those who smoke beyond 25 pack-years, which may have a direct toxic effect on the intrinsic healing capability of the spinal cord,6 which reflects back to our current smokers study cohort, who reported a median of 24 (13, 36) pack-years at baseline,2 hindering pain relief; as for every extra one pack-day, a decrease in pain by 1.23 Numerical Rating Scale (NRS) units (95% CI −2.59 to 0.13; p=0.023) was found. Moreover, on the impact of smoking abstinence, we found that one more year of quitting smoking was associated with a 0.6-unit decrease (95% CI −1.65 to 0.43; p=0.090) in NRS pain scores after SCS implant, adjusting for all potential confounders 2.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…This is particularly true for those who smoke beyond 25 pack-years, which may have a direct toxic effect on the intrinsic healing capability of the spinal cord,6 which reflects back to our current smokers study cohort, who reported a median of 24 (13, 36) pack-years at baseline,2 hindering pain relief; as for every extra one pack-day, a decrease in pain by 1.23 Numerical Rating Scale (NRS) units (95% CI −2.59 to 0.13; p=0.023) was found. Moreover, on the impact of smoking abstinence, we found that one more year of quitting smoking was associated with a 0.6-unit decrease (95% CI −1.65 to 0.43; p=0.090) in NRS pain scores after SCS implant, adjusting for all potential confounders 2.…”
mentioning
confidence: 70%
“…Moreover, on the impact of smoking abstinence, we found that one more year of quitting smoking was associated with a 0.6-unit decrease (95% CI −1.65 to 0.43; p=0.090) in NRS pain scores after SCS implant, adjusting for all potential confounders 2. Additionally, as Drs Knezevic and Candio1 mentioned, not only was the pain relief experienced among smokers at 12 months minimal, furthermore the median opioid consumption increased,2 which emphasizes the importance of smoking cessation.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…One recently identified subgroup that may be at risk of poor outcomes are smokers treated with SCS. In a retrospective study that involved 213 patients with chronic spine-related pain treated with SCS, smokers reported greater pain intensity and consumed greater quantities of opioids compared with nonsmokers at 1 year following SCS implant 2. More specifically, the pain scores of smokers were 37% greater compared with never smokers, and the median morphine equivalent dose of smokers was 40 mg compared with 23 mg in never smokers 2 3.…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective study that involved 213 patients with chronic spine-related pain treated with SCS, smokers reported greater pain intensity and consumed greater quantities of opioids compared with nonsmokers at 1 year following SCS implant 2. More specifically, the pain scores of smokers were 37% greater compared with never smokers, and the median morphine equivalent dose of smokers was 40 mg compared with 23 mg in never smokers 2 3. This is critically important because SCS is one of the few treatments associated with sustained and durable pain relief, and low risk of adverse effects 1…”
Section: Introductionmentioning
confidence: 99%